VisTCR: An Interactive Software for T Cell Repertoire Sequencing Data Analysis - Ni, Qingshan; Zhang, Jianyang; Zheng, Zihan; Chen, Gang; Christian, Laura; Grönholm, Juha; Yu, Haili; Zhou, Daxue; Zhuang, Yuan; Li, Qi-Jing; Wan, Ying (Frontiers in Genetics, 2020)
Recent progress in high throughput sequencing technologies has provided an opportunity to probe T cell receptor (TCR) repertoire, bringing about an explosion of TCR sequencing data and analysis tools. For easier and more heuristic analysis TCR sequencing data, we developed a client-based HTML program (VisTCR). It has a data storage module and a data analysis module that integrate multiple cutting-edge analysis algorithms in a hierarchical fashion. Researchers can group and re-group samples for different analysis purposes by customized “Experiment Design File.” Moreover, the VisTCR provides a user-friendly interactive interface, by all the TCR analysis methods and visualization results can be accessed and saved as tables or graphs in the process of analysis. The source code is freely available at https://github.com/qingshanni/VisTCR.